Analisis Fitokimia Teh Celup Herbal Ditinjau dari Suhu Pengeringan: Phytochemical Analysis of Herbal Teabags Based on Drying Temperature - Bahar, Asrul; Romadhoni, Ita Fatkhur; Iriyani, Dwi (Amerta Nutrition, 2025)
Background: The potential for diversifying herbal beverages by combining mangosteen peel, red ginger, lemongrass, cherry leaves, orange leaves, and bay leaves into ready-to-drink herbal tea is substantial. Nonetheless, additional examination of the phytochemical composition post-drying is required. Objectives: This study seeks to ascertain the phytochemical composition, including total phenols, flavonoids, and antioxidants, influenced by differences in the drying temperature of herbal tea bags. Methods: The study employed an experimental design with differing drying temperatures: M1 (45°C), M2 (55°C), M3 (65°C), M4 (75°C), M5 (85°C). Data were gathered through observations by 100 panelists and subsequently analyzed using parametric statistics in SPSS, with a significance level of 5%. The phytochemical test was conducted at the Industrial Research and Standardization Center at Jagir Wonokromo Street No. 360, Tenggilis Mejoyo, Surabaya. Results: The drying treatment of herbal tea bags M1 at 45°C exhibited the highest antioxidant activity, measuring 216.02 µg/mL, with an IC50 value of 46.17 ppm, a moisture content of 7.20%, a yield of 13.15%, a total phenolic content of 134.2 mgGAE/g, and a total flavonoid content of 81.33 mgQE/g. It is characterized by a yellow hue, a distinct herbal aroma, and a blend of ginger and lemongrass spices, ultimately meeting the preferred acceptance criteria. Conclusions: The drying temperature influences the phytochemical composition and the preferences of panelists for herbal tea bags, including mangosteen peel, red ginger, lemongrass, cherry leaves, lime leaves, and bay leaves.